ANALYSIS OF EMPLOYEE PERFORMANCE: ORGANIZATIONAL CULTURE AND TRANSFORMATIONAL LEADERSHIP - Herlina Lusiana (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This study intends to examine the effects of organizational culture and transformational leadership on employee performance at PT. Sumber Digital Media Tanaka Banjarmasin Elektronik, either independently or combined. The sample included 37 employees using saturated sampling criteria. This kind of research is explanatory and employs a quantitative methodology. The research method employs an online survey that is graded on a Likert scale. The validity, reliability, and traditional assumptions were validated using the SPSS version 23 research tool. Moreover, verify your hypothese. The findings demonstrated that transformational and corporate cultures at PT. Sumber Digital Media Tanaka Banjarmasin Elektronik significantly affected employee performance, either wholly or partially. Keywords: organizational culture, transformational leadership, employee performance